Use of industrially significant limonium gmelinii plants for medicinal aims (Eurasian Journal of Ecology, 2016)
Priority for use of plant material, which has recoverable reserves in Kazakhstan, is marked in this article. The object of the study is Limonium gmelinii - plant, used for the production of medicinal products, namelysubstance “Limonidin”, released from the roots of the plant in the form of dry extract, as well as ointment, syrup and tincture of the same name, “Limonidin”. The above formulations were introduced in medicine asa highly drugs, having high latitude of therapeutic action, low toxicity, absence of allergic and cumulative reactions.
Keywords: Limonium gmelinii; biochemical activity; medicinal preparation; substance; ointment; syrup; tincture; biological activity.